Lethality of patients with rheumatoid arthritis depending on adalimumab administration: imitation modeling - D V Goryachev; Sh. F. Erdes (Научно-практическая ревматология, 2009)
Lethality of pts with rheumatoid arthritis (RA) exceeds mortality values in general population. Possibility of disease modifying anti-rheumatic drugs (DMARD) influence on RA pts lethality has been widely discussed lately in scientific works. Objective. To determine possible lethality diminishment in Russian population of RA pts with one of biological drugs TNFα antagonist adalimumab. Material and methods. Model construction is based on the fact of lethality dependence on pt functional state assessed by HAQ. Model simulating progression of functional disability in pts with RA visiting medical institutions of Russia was made (RAISER study). 3 model variants for imitation of consecutive change of DMARDs including adalimumab were done. First consecution assessed DMARD change in the next chain: adalimumab-methotrexate-sulfasalazine-leflunomide-azathioprine-cyclosporine-palliative therapy. Second consecution: adalimumab administration after failure of first 3 DMARDs. Third consecution considered only change of synthetic DMARDs without adalimumab inclusion. Model imitated participation of 3000 pts in every consecution. Prognosis horizon was 12 years. Age of pts and initial HAQ distribution were get from results of epidemiological RAISER study. Calculation was done on the base of elevation of standardized lethality level (SLL) in population of RA pts in average from 135% to 300%. SLL values from 80 to 320% were used depending on functional disability degree with converting to Russian values of age-specific lethality coefficient for 1999. Results. Lethality in treatment consecutions including adalimumab was significantly lower. To the end of 12th year in group not using adalimumab, using it at once and using it after 376 DMARDs respectively 65,1%, 71,6% and 71,1% of pts were still alive. Conclusion. Significant decrease of lethality with adalimumab inclusion in consecution of DMARD change during treatment of RA pts was demonstrated with imitation modeling method.